DEPICTION OF FEMALE SEXUALITY IN RUSSIAN LITERATURE AT THE END OF THE 19TH AND THE BEGINNING OF THE 20TH CENTURY (Slavic Studies, 2025)
This study examines how female sexuality is portrayed in Russian literature at the turn of the 19th to the 20th century, focusing on works by authors such as Tolstoy, Zinaida Gippius, Lydia Zinovyeva-Annibal, and Alexander Kuprin. It highlights how literary texts both reflect and challenge prevailing patriarchal norms by depicting women’s sexual desires, autonomy, and self-determination against the backdrop of rapid social, economic, and cultural changes. By exploring themes such as the objectification and eroticization of the female body, psychological transformations prompted by sexual awareness, and the struggle between personal identity and societal expectations, the analysis reveals literature’s role in questioning traditional gender roles. Ultimately, these works offer insight into the evolving understanding of female sexuality during a time of profound historical upheaval and set the stage for reevaluating gender dynamics in both past and present contexts.
Keywords: Russian literature; female sexuality; authonomy; self awereness; gender dynamics